Preoperative Emergency Department Visits Are Predictive of 90-Day Postoperative Emergency Department Visits and Discharge Disposition in Total Knee Arthroplasty Patients - Kiskaddon, Eric M.; Soehnlen, Neil T.; Erb, Eric; Froehle, Andrew W.; Green, Uthona; Krishnamurthy, Anil (The Journal of Knee Surgery, 2020)
The increasing number of patients undergoing total knee arthroplasty (TKA) has resulted in efforts to better understand patient utilization of healthcare services in the 90-day postoperative period. The primary purpose of this study was to examine whether emergency department (ED) visits in the year prior to elective TKA were predictive of postoperative ED visits in the 90-day global period following surgery. A retrospective chart review was performed for all patients undergoing TKA from June 1, 2011 to December 31, 2015 at a Veterans Affairs hospital. Total number of ED visits in the year prior to surgery and 90 days following surgery were tabulated. Binary and ordinal logistic regression analyses were utilized to determine if preoperative ED visits were predictive of postoperative ED visits. The significance level was set to α = 0.05. Overall, 611 eligible TKA procedures were performed. The logistic regression model for postoperative ED visits was significant (p < 0.001), with the number of preoperative ED visits (1 vs. 0: p < 0.001; 2 vs. 1: p = 0.012) and presence of diabetes (p = 0.007) both predicting the likelihood of a postoperative ED visit. Healthcare changes that are redefining the concept of quality of care to include the postoperative care episode, coupled with an increasingly aging population in need of TKA, will continue to challenge orthopaedic surgeons to provide safe, competent, and cost-effective care to patients. The results of this study demonstrate that a patient's propensity to visit the ED prior to TKA is predictive of a tendency to do so postoperatively and is of use to surgeons when evaluating and counselling patients who will be undergoing a TKA.
Keywords: total knee arthroplasty; emergency department visits; quality of care